2019
DOI: 10.17511/jopm.2019.i09.20
|View full text |Cite
|
Sign up to set email alerts
|

An unusual presentation of a granulosa cell tumor in broad ligament: morphological features and close differential

Abstract: Background: Though Granulosa cell tumors (GCTs) are the most common ovarian sex cord stromal tumors, they are very rare in extra ovarian sites with a handful of cases reported in retroperitoneum, broad ligament, fallopian tube, mesentery and even in the adrenals. Female Adnexal Tumor of probable Wolffian Origin (FATWO), which is also a very rare tumor comes up as its closest differential because of a significant overlap of topographic, morphologic, and immunohistochemical (IHC) features. Case Summary: Present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Studies using subunit specific ELISA show inhibin B to be the major form secreted in GCT, and that inhibin B is more accurate than inhibin A in detecting GCT. 14 Studies have further confirmed that inhibin B is a sensitive and specific marker for GCTs. 16,17 Thus, inhibin B levels can be helpful in the early detection and recurrence of GCTs.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Studies using subunit specific ELISA show inhibin B to be the major form secreted in GCT, and that inhibin B is more accurate than inhibin A in detecting GCT. 14 Studies have further confirmed that inhibin B is a sensitive and specific marker for GCTs. 16,17 Thus, inhibin B levels can be helpful in the early detection and recurrence of GCTs.…”
Section: Discussionmentioning
confidence: 92%
“…13 Serum inhibin levels are elevated in GCT thus, inhibin can be used as a marker for GCT. 14 Lappohn et al 15 was the first to demonstrate the value of inhibin as a marker for both primary and recurrent disease and showed that a rise in inhibin level preceded clinical recurrence as early as 20 months. Studies using subunit specific ELISA show inhibin B to be the major form secreted in GCT, and that inhibin B is more accurate than inhibin A in detecting GCT.…”
Section: Discussionmentioning
confidence: 99%